(untitled) (Scientific journal of the Fergana State University, 2023)
The article discusses the specific methods of interpretation of words, research, interpretation of words at a new stage in the development of Uzbek national lexicography.The lexicographical explanation of nominal units, expressing the notions of the national ideas and their incorporating into the new explanatory dictionaries gives the opportunity of presenting the successes of the new progressive period.